Optimizing subgrade design for blowing snow prevention: a CFD-based parametric study - Liu, Jie; He, Zhihao; Wang, Yong; Wang, Fenglong; Yang, Zhiwei (Frontiers in Earth Science, 2026)
Blowing snow poses a serious threat to highway traffic safety, and appropriate subgrade cross-sectional designs can effectively mitigate the impacts. Systematic studies on how to optimize subgrade structural design to maximize the mitigation of blowing snow disasters are still lacking. To address this, this paper investigates the fundamental parameters of two typical subgrades: embankments and cuttings. To investigate the influence of varying subgrade cross-sectional configurations and slope ratios on the effectiveness of blowing snow control with a focus on single-parameter variations, this study employs CFD (computational fluid dynamics) simulations to analyze velocity contour distributions, snow accumulation patterns, and vertical wind velocity profiles around the models. The results demonstrate that implementing gentle slopes for subgrades (including both embankments and cuttings) or appropriately widening snow accumulation platforms of the cutting can effectively mitigate snow deposition on pavement surfaces. When wind flows through the cutting, the overall wind velocity profile exhibits a W-shaped distribution pattern. Meanwhile, variations in its depth and slope ratio both exhibit positive correlations with road snow accumulation. Furthermore, three embankment models with cross-sectional dimensions identical to those of field conditions but varying heights are established. Through combined field monitoring tests and numerical simulations, wind velocities are systematically measured at ten vertical elevations for all critical locations. Comparative results demonstrate that the flow field distribution patterns and variation trends observed in the field are highly consistent with the numerical simulation results, thereby validating the reliability of the numerical model. This research elucidates the underlying physical mechanisms of how subgrade structural parameters mitigate the impact of snowdrift disasters, providing scientifically validated references for hazard reduction along transportation corridors.